2015
DOI: 10.4238/2015.july.13.20
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, characterization, and expression of Rab5B, Rab6A, and Rab7 from Litopenaeus vannamei (Penaeidae)

Abstract: ABSTRACT. The Rab protein family belongs to a superfamily of ras-like GTP-binding proteins. Rab proteins regulate many steps of membrane trafficking. In this study, three Rab family members, Rab5B, Rab6A, and Rab7, designated LvRab5B, LvRab6A, and LvRab7, were cloned from Litopenaeus vannamei. The full-length cDNA sequences of LvRab5B, LvRab6A, and LvRab7 were 1383, 873, and 767 nucleotides in length and they encoded proteins of 211, 212, and 205 amino acids, respectively. Using qRT-PCR, the mRNA expression le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Since there are many cascades for phagocytosis and various molecules work together, it is difficult to determine which cluster is centralized, but various phagocytosis-related genes are expressed relatively strongly in Hem 5 ( Figure 8—figure supplement 4 ). Rab7 was found to be highly expressed in Hem 1, which is known to be involved in the endosomal trafficking pathway of virus-infected penaeid shrimp ( Zhao et al, 2015 ). However, there have been no detailed functional studies of Rab7 on whether it is involved in phagocytosis in shrimp, so it is early to determine its role in Hem 1.…”
Section: Resultsmentioning
confidence: 99%
“…Since there are many cascades for phagocytosis and various molecules work together, it is difficult to determine which cluster is centralized, but various phagocytosis-related genes are expressed relatively strongly in Hem 5 ( Figure 8—figure supplement 4 ). Rab7 was found to be highly expressed in Hem 1, which is known to be involved in the endosomal trafficking pathway of virus-infected penaeid shrimp ( Zhao et al, 2015 ). However, there have been no detailed functional studies of Rab7 on whether it is involved in phagocytosis in shrimp, so it is early to determine its role in Hem 1.…”
Section: Resultsmentioning
confidence: 99%
“…Another small GTPase involved in endosomal trafficking, Rab7, is apparently vital for WSSV replication 180 . Rab7 also interacts with the VP28 protein and is involved in antiviral immune defence against WSSV and infectious hypodermal and haematopoietic necrosis virus (IHHNV) 181,182 . Although small GTPases are implicated in innate immunity, their role in regulating metabolic reprogramming is largely unknown.…”
Section: Signaling Pathways That Regulate Metabolismmentioning
confidence: 99%
“…In crustaceans, Rab proteins are gradually being studied, which have been proven to participate in antiviral immunity. Rab5B, Rab6A and Rab7 were firstly cloned in Litopenaeus vannamei , and the mRNA expression of LvRab5B, LvRab6A and LvRab7 in the hepatopancreas was significantly up-regulated after infection with infectious hypodermal and hematopoietic necrosis virus or WSSV, implying that LvRab5B, LvRab6A and LvRab7 might be involved in immune response towards viral infection in crustacean [45] . Furthermore, Rab7 has been reported to bind to the WSSV envelope protein VP28 in a dose-dependent manner, and vivo neutralization assay showed that compared with the control group injected with WSSV, the shrimp mortality of the groups injected with WSSV plus the recombinant Pm Rab7 (15%) or WSSV plus anti-Rab7 antibody were both significantly decreased, which suggested that the binding of endogenous Pm Rab7 with VP28 was necessary for WSSV infection in P. monodon , and Pm Rab7 might help WSSV infection by avoiding the degradation of lysosome [46] .…”
Section: Molecular Regulation Of Autophagy In Crustaceansmentioning
confidence: 99%